Re- visiting the Roman Iron Age Hoby chieftain burial after 100 years of its discovery - adding the strontium isotopic perspective - Frei, Karin Margarita; Klingenberg, Susanne (Danish Journal of Archaeology, 2022)
In 1920 on the island of Lolland, in southern Denmark the remains of one of northern Europe’s richest graves came to light, the Hoby chieftain burial. It revealed a large number of luxurious Roman goods, including two silver drinking cups decorated with Greek-inspired scenes from Homer’s Iliad. The burial dates to the beginning of the Roman Iron Age (1CE -200CE), and represents a key point in time when the Roman Empire failed to expand towards the north and changed its strategy towards a more political and diplomatic type of relationship with northern Europe. Hence, the Hoby burial is considered to be a key example of this type of relationship. We revisited the burial and present the first strontium isotope analyses of the human remains of the Hoby individual from three of his teeth and 10 additional environmental samples to shed light on his provenance. We discussed these results in light of the new insights provided by recent excavations of a contemporary nearby settlement. Our results indicate that the Hoby individual was most probably of local origin, corroborating previous interpretations. Furthermore, the associated settlement seems to confirm the central role of Hoby in the Early Roman Iron Age society.